Floristic and vegetation structure of a grassland plant community on shallow basalt in southern Brazil - Pinto, Marcelo Fett; Nabinger, Carlos; Boldrini, Ilsi Iob; Ferreira, Pedro Maria de Abreu; Setubal, Robberson Bernal; Trevisan, Rafael; Fedrigo, Jean Kássio; Carassai, Igor Justin (Acta botânica brasilica, 2013)
Few studies have adequately described the floristic and structural features of natural grasslands associated with shallow basalt soils in southern Brazil. This study was carried out on natural grazing land used for livestock production in the municipality of Santana do Livramento, in the Campanha region of the state of Rio Grande do Sul, Brazil. The aim of the study was to describe the floristic and structural diversity of the area. The floristic list obtained comprises 229 plant taxa from 40 botanical families, with a predominance of the families Poaceae (62), Asteraceae (28), Fabaceae (16) and Cyperaceae (12). The estimated diversity and evenness in the community were 3.00 and 0.874, respectively. Bare soil and rock outcrops accounted for 19.3% of the area, resulting in limited forage availability. Multivariate analysis revealed two well-defined groups among the sampling units. One group showed a high degree of internal aggregation, associated with deep soils, and was characterized by the presence of tussocks, whereas the other was less aggregate and was characterized by prostrate species growing on shallow soil. Ordination analysis indicated a gradient of moisture and of soil depth in the study area, resulting in different vegetation patterns. These patterns were analogous to the vegetation physiognomies described for Uruguayan grasslands. Overall, the grassland community studied is similar to others found throughout southern Brazil, although it harbors more winter forage species. In addition, the rare grass Paspalum indecorum Mez is locally dominant in some patches, behaving similarly to P. notatum Fl., a widespread grass that dominates extensive grassland areas in southern Brazil.